PERANAN IKATAN MAHASISWA MUHAMMADIYAH (IMM) DALAM MEMBENTUK PERILAKU BERAGAMA MAHASISWA DI PERGURUAN TINGGI MUHAMMADIYAH - Imam Pribadi (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2016)
This thesis is aimed to describe the role of Ikatan Mahasiswa Muhammadiyah (IMM) in changing the religious behavior of the students of Perguruan Tinggi Muhammadiyah Palopo, in which its problem is described in three sub-problems, as follows: to find out the role of Darul Arqam Dasar, Darul Arqam Madya, and Islamic studies toward the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo, to find out the supporting factors and the obstacles of the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo, to find out the solution to cope with the obstacles of the change of the students' religious behavior at Perguruan Tinggi Muhammadiyah Palopo.This research is a qualitative research with primary data source taken from Perguruan Tinggi Muhammadiyah Palopo through the interviews with the main informants, and the secondary data are the literatures and the related questionnaires. The data collecting instrument is the researcher as human instrument to determine the research focus, to collect the data, to assess the data quality, to interpret the data, and to make conclusion. The interview guide, observation, and documents are the complements.The findings and the data analysis show that there is a significant influence of the formal trainings and Islamic studies of Ikatan Mahasiswa Muhammadiyah (IMM)